Olympic Weightlifting Center
One of the most impressive facilities that HASTC can offer visiting athletes is the Walkup Skydome's 4,500 square foot, state-of-the-art Olympic weightlifting center. This facility, one of the finest of its kind in the United States, is a USA Weightlifting Regional Training Center and services all Southwestern states. The weight room is Olympic weightlifting-based and features a diverse complement of strength training equipment, as well as has the capacity to carry out advanced plyometric and speed conditioning drills. Many skills training services are available as well, including the design and implementation of strength and conditioning programs (based on Olympic-style weightlifting) by certified USA Weightlifting coaches.